The new Romanian cinema - Stojanova, Christina; Duma, Dana (Traditions in world cinema., 2019)
Covering more than 40 films made since 2001 -- including "The Death of Mr Lǎzǎrescu," "The Paper Will Be Blue," and "Beyond the Hills" -- this pioneering collection is the first to contextualize New Romanian Cinema aesthetically, theoretically and historically. The book examines its approach to national and gender identity, and its unique convergence of ethics and aesthetics. With thorough bibliographic and filmographic references, and a comprehensive historical overview, the anthology is a systematic guide to New Romanian Cinema as a consolidated movement, highlighting its potential as a rich interdisciplinary field of study